Pengaruh Tingkat Likuiditas dan Risiko Kredit Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) Di Kecamatan Kerambitan - Sari, Ni Putu Wina Merta; Kusumawati, Ni Putu Ayu; Pratiwi, Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2025)
LPD is a financial institution established for the benefit of the pekraman village, aiming to improve the welfare of the community. LPD has a companion agency assigned by the Governor. namely the LPLPD. In Kabupaten Tabanan, there is an increase in the number of unhealthy LPDs due to problematic credits and insufficient financial ratios. Kecamatan Kerambitan, a district in Kabupaten Tabanan, also has several unhealthy LPDs. Furthermore, the ROA generated by LPDs in Kecamatan Kerambitan has significantly decreased from 2020 to 2022, with the lowest values compared to other districts in  Kabupaten Tabanan. This research was conducted at LPDs throughout Kerambitan District, Tabanan Regency for the 2020-2022 period. The number of samples used was 26 LPDs using a probability sampling method with saturated sample technique. The type of data used is secondary data obtained from the Tabanan Regency LPD Empowerment Institute for the 2020-2022 period. Data collection methods are non-participant observation and documentation methods. The research uses multiple linear regression analysis. Based on the results of this research analysis, it shows that: (1) Liquidity has a negative and non  significant effect on LPD profitability in Kerambitan District, (2) Credit Risk has a negative and significant effect on LPD profitability in Kerambitan District. LPD is a financial institution established for the benefit of the pekraman village, aiming to improve the welfare of the community. LPD has a companion agency assigned by the Governor. namely the LPLPD. In Kabupaten Tabanan, there is an increase in the number of unhealthy LPDs due to problematic credits and insufficient financial ratios. Kecamatan Kerambitan, a district in Kabupaten Tabanan, also has several unhealthy LPDs. Furthermore, the ROA generated by LPDs in Kecamatan Kerambitan has significantly decreased from 2020 to 2022, with the lowest values compared to other districts in Kabupaten Tabanan. This research was conducted at LPDs throughout Kerambitan District, Tabanan Regency for the 2020-2022 period. The number of samples used was 26 LPDs using a probability sampling method with saturated sample technique. The type of data used is secondary data obtained from the Tabanan Regency LPD Empowerment Institute for the 2020-2022 period. Data collection methods are non-participant observation and documentation methods. The research uses multiple linear regression analysis. Based on the results of this research analysis, it shows that: (1) Liquidity has a negative and non significant effect on LPD profitability in Kerambitan District, (2) Credit Risk has a negative and significant effect on LPD profitability in Kerambitan District.